STOMATOLOGICAL/DENTAL FEATURES OF VITAMIN D RESISTANT AND VITAMIN D DEPENDENT RICKETS - Margvelashvili, Vladimer; Taboridze, Iamze; Aladashvili, Lali; Japaridze, Nino (European Scientific Journal, ESJ, 2014)
The aim of the study is an investigation of stomatological/dental characteristics at vitamin D resistant and vitamin D dependent rickets. Materials and methods: The study was based on the results obtained after investigation of 13 patients 0-18 of ages with D vitamin resistant rickets (I group) and 68 patients with D vitamin-dependent rickets (II group) and 61 children of control group. Physical development, dental status and biochemical features of the mentioned children have been studied. Methods of the study: anamnesis, clinical examination, X-ray examination, blood and urine biochemical analysis. Quantity data were compared according to - t (student) criteria and qualitative data – according to - F (fisher) criteria. Clinical data were processed with statistical programs package SPSS 22. Results: The incidence rates of insufficient physical development (physical retardation), body constitutional disorder, jaw shape, occlusion and teeth constitutional anomalies as well as delayed teeth eruption are significantly higher at vitamin D resistant rickets in comparison with vitamin D-dependent rickets and control group. The incidence rate of enamel hypoplasia in group of vitamin D resistant rickets is 0.69, vitamin D dependent group - 0.07(p>0.000) and control group – 0,03( p>0.000), respectively, the rate of periapical abscesses with canal orifice – in group of vitamin D-resistant rickets equals to 0.31, vitamin D-dependent group – 0.06(p=0.054), and control group - 0.10(p=0.0457), respectively, which is significantly higher in comparison with the dependent rickets and control groups. Among the children with vitamin D resistant rickets, average caries intensity (DMF) index and average PMA index p>0.05 are reliably higher in comparison with vitamin D dependent rickets. Tubular phosphate reabsorption reveals positive correlation with DMF index – r =0.57, p = 0.0380; PMA index - r=0.84, p=0.0003; reduction of tubular phosphate reabsorption correlates with caries r=0.6770, p=0.0110; pulpitis r =0.6770, p =0.0110; periodontitis r=0.6770, p=0.0110. Conclusion: At vitamin D resistant rickets the dental anomalies, being in correlation with metabolic disorder, occur.